Surprising spectra of root-associated fungi in submerged aquatic plants - Kohout, Petr; Sýkorová, Zuzana; Ctvrtlíková, Martina; Rydlová, Jana; Suda, Jan; Vohník, Martin; Sudová, Radka (FEMS microbiology ecology, 2012)
Similarly to plants from terrestrial ecosystems, aquatic species harbour wide spectra of root-associated fungi (RAF). However, comparably less is known about fungal diversity in submerged roots. We assessed the incidence and diversity of RAF in submerged aquatic plants using microscopy, culture-dependent and culture-independent techniques. We studied RAF of five submerged isoetid species collected in four oligotrophic freshwater lakes in Norway. Levels of dark septate endophytes (DSE) colonization differed among the lakes and were positively related to the organic matter content and negatively related to pH. In total, we identified 41 fungal OTUs using culture-dependent and culture-independent techniques, belonging to Mucoromycotina, Chytridiomycota, Glomeromycota, Ascomycota as well as Basidiomycota. Sequences corresponding to aquatic hyphomycetes (e.g. Nectria lugdunensis, Tetracladium furcatum and Varicosporium elodeae) were obtained. Eight arbuscular mycorrhizal taxa belonging to the orders Archaeosporales, Diversisporales and Glomerales were also detected. However, the vast majority of the fungal species detected (e.g. Ceratobasidium sp., Cryptosporiopsis rhizophila, Leptodontidium orchidicola, and Tuber sp.) have previously been known only from roots of terrestrial plants. The abundance and phylogenetic distribution of mycorrhizal as well as nonmycorrhizal fungi in the roots of submerged plants have reshaped our views on the fungal diversity in aquatic environment.
Keywords: Basidiomycota; Mycorrhizae; Plants; Fungi; Ecosystem; fylogeneze; Lakes; Phylogeny; endofyty; Plant Roots; Norway; houby; jezera; rostliny; kořeny rostlin; ekosystém; Ascomycota; Norsko; mykorhiza; Endophytes